2009
DOI: 10.1002/asna.200811184
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate‐term variations in solar radius during solar cycle 23

Abstract: In this study, we look for the mid-term variations in the daily average data of solar radius measurements made at the Solar Astrolabe Station of TUBITAK National Observatory (TUG) during solar cycle 23 for a time interval from 2000 February 26 to 2006 November 15. Due to the weather conditions and seasonal effect dependent on the latitude, the data series has the temporal gaps. For spectral analysis of the data series, thus, we use the Date Compensated Discrete Fourier Transform (DCDFT) and the CLEANest algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…The geomagnetic A p index exhibited prominent 60.64, 91.49 days peaks, while the solar flare data showed 63.73, 67.69 and 98.15 days peaks during the rising branch of cycle 23 (Lou et al 2003). Kiliç et al (2009) ing 1989-1990, corresponding to a maximum phase of cycle 22 and this result is within our investigation. In the intermediate range our study shows the existence of 120-130 days, ≈160-170 days, ≈240-256 days, ≈1.09 yr. and ≈1.2 yr. periodicities in different data sets in different time intervals.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The geomagnetic A p index exhibited prominent 60.64, 91.49 days peaks, while the solar flare data showed 63.73, 67.69 and 98.15 days peaks during the rising branch of cycle 23 (Lou et al 2003). Kiliç et al (2009) ing 1989-1990, corresponding to a maximum phase of cycle 22 and this result is within our investigation. In the intermediate range our study shows the existence of 120-130 days, ≈160-170 days, ≈240-256 days, ≈1.09 yr. and ≈1.2 yr. periodicities in different data sets in different time intervals.…”
Section: Discussionsupporting
confidence: 62%
“…The ≈2.7 and ≈3.7 months fluctuation have also been noted in cosmic ray intensities during cycle 21 ) and the Homestake solar neutrino time-series (Liritzis 1995). The solar diameter also exhibits intermediate-term periodicities of ≈117, ≈125, ≈172 and ≈195 days during cycle 23 (Kiliç et al 2009). Knaack et al (2005) made an extensive time-series analysis of photospheric magnetic flux data reported by the NSO/Kitt peak for 1975 to 2003, covering solar cycles 21, 22 and a part of cycle 23, by the wavelet method and found a multitude of quasi-periodic oscillations.…”
Section: Discussionmentioning
confidence: 95%
“…Bai (2003) thought the regime between 27 days and 11 years can be called a "midrange" period, such as in the sunspot blocking function, 10.7 cm radio flux, sunspot numbers, coronal emission intensity (Deng et al 2012), plage index (Lean & Brueckner 1989), sunspot areas and Zurich sunspot numbers (Oliver et al 1992); and quasi-periodic oscillation in the photospheric magnetic field (Knaack et al 2005); sunspot number, CaII area and K index, Lyman α, 2800 MHz radio emission, coronal green-line index, solar magnetic field (Kane 2005); total solar irradiance (Li et al 2012); filament (Kong et al 2014) and polar faculae (Deng et al 2014). A spectral analysis of intermediate-term variations of the solar radius at TUBITAK National Observatory from 2000 February 26 to 2006 November 15 by Kilic ¸et al (2009) also found extensive mid-term periodicities at 393.2, 338.9, 206.5, 195.2, 172.3 and 125.4 days. The 319 and 359 day periodicities correspond to the approximately one-year variation, which has been found earlier in the solar radius (Delache et al 1985;Gavryusev et al 1994;Moussaoui et al 2001).…”
Section: Analysis Resultsmentioning
confidence: 99%
“…Hence, traditional Fourier analysis is not suitable for analyzing our solar radius data. In addition, non-uniform data with large gaps can generate false peaks in the power spectrum, and the ghost peaks can even be larger than the real components (Kilic ¸et al 2009).…”
Section: Hilbert-huang Transformmentioning
confidence: 99%
See 1 more Smart Citation